2021
DOI: 10.1111/ajco.13592
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term clinical outcomes of stereotactic radiosurgery and hypofractionated stereotactic radiotherapy using the CyberKnife® robotic radiosurgery system for vestibular schwannoma

Abstract: Aim The study aimed to evaluate the long‐term clinical outcomes of patients with vestibular schwannoma (VS) treated with stereotactic radiosurgery (SRS) and hypofractionated stereotactic radiotherapy (HSRT) with frameless robotic whole‐body radiosurgery system (CyberKnife®). Methods This retrospective analysis of prospectively collected data included 123 consecutive patients with VS treated at the Radiosurgery center, Ramathibodi Hospital, Bangkok, Thailand. SRS was recommended for patients with unserviceable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In a meta-analysis published in 2017, the mean LCR was 96.3%, according to the results of 11 studies involving 800 patients in which CK-SRT was applied [21]. In another recently published study examining 123 patients who underwent CK-SRT with a median extended follow-up of 6 years, 5-y, and 8-y progression-free survival was reported to be 96% and 92% [22]. In light of these studies, it is possible to say that there are similar and excellent LCR in terms of both GK and CK-based radiosurgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis published in 2017, the mean LCR was 96.3%, according to the results of 11 studies involving 800 patients in which CK-SRT was applied [21]. In another recently published study examining 123 patients who underwent CK-SRT with a median extended follow-up of 6 years, 5-y, and 8-y progression-free survival was reported to be 96% and 92% [22]. In light of these studies, it is possible to say that there are similar and excellent LCR in terms of both GK and CK-based radiosurgery.…”
Section: Discussionmentioning
confidence: 99%
“…Tamura et al [29] suggested that serviceable hearing can be preserved in patients with good hearing function at the beginning, under the age of 50, and whose cochlea dose did not exceed 4 Gy. Hearing protection was reported to be over 50% in CK SRT studies [19,21,22]. However, these results may be misleading due to the small number of patients, the relatively small tumor diameter, and the inadequacy of audiogram examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Fractionated dosing is theoretically safer for the vestibulocochlear nerve and cochlea than a single large radiosurgical dose and might improve treatment outcomes, particularly hearing and facial/trigeminal nerve function outcomes. Although treatment of sporadic VSs using HSRT has been previously reported [11], the role of HSRT for treating VS-NF2 is unclear. To the best of our knowledge, this is the rst study to report long-term clinical outcomes of HSRT treatment of VS-NF2.…”
Section: Discussionmentioning
confidence: 99%
“…The 46 remaining articles had their full text read, and 33 were excluded due to the following reasons: the hearing classification system specified in the eligibility criteria was not used or it was used inadequately (for example: considering GR grade III or AAO-HNS class C as serviceable hearing); [15][16][17][18][19] inadequate study design; [20][21][22][23] incomplete study; [24][25][26][27][28][29][30][31][32][33][34] use of another radiation source; 35,36 same population from others studies; [37][38][39][40][41] and inadequate data report [42][43][44][45][46][47] (the corresponding authors of these studies were contacted to request additional information, but there was no response). Then, a total of 13 studies [48][49][50][51][52][53][54][55][56][57][58][59][60] we...…”
Section: Study Selectionmentioning
confidence: 99%